Kajian Hukum Model Penyelesaian Kasus Melalui Hukum Pidana Adat Sebagai Upaya Penyelesaian Sengketa Di Luar Pengadilan - Sinaga, Miduk; Warman, Edi; Eddy, Triono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to find out the legal arrangements for implementing customary law in Indonesia and the process of resolving criminal cases through customary criminal law as an effort to settle disputes outside the court. This study uses normative legal research specifications, using qualitative data analysis with a doctrinal legal approach, collecting data by means of literature studies and interviews. The results of the research show that the application of adat has received recognition from several instruments, including Article 18 B paragraph (2) of the 1945 Constitution, Article 5 paragraph (3) of the Emergency Law of the Republic of Indonesia Number 1 of 1951 and Article 15 paragraph (2) of the International Covenant on Civil and Political Rights (ICCPR). Circular of the Chief of Police Number: SE/8/VII/2018, Director General of Legal Entities for the General Court of the Republic of Indonesia No: 1691/DJU/SK/PS.00/12/2020 and Regulation of the Attorney General of the Republic of Indonesia No. 15 of 2020 which regulates that certain crimes can be resolved through a Restorative Justice mechanism. The Process of Settlement of the beating/fighting that occurred around 2001 in Sosordolok Village, Kec. Daily, Kab. Samosir, a young man A (perpetrator) beat youth B (victim), the problem was that the mediator was Raja Bius), Mr. Monang Sinaga as a trusted party as an intermediary or mediator. The process of resolving the case was carried out at the Sosordolok village hall ending in peace, then a kind of "Mangindahani" was carried out, meaning "giving food" and paying medical expenses to the victim.